2021
DOI: 10.1039/d1ra03634c
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired pressure-sensitive adhesive: evaluation of the effect of dopamine methacrylamide comonomer as a general property modifier using molecular dynamics simulation

Abstract: The use of catechol-containing comonomers as a general property enhancer to achieve unique properties has received particular attention for designing bioinspired polymeric materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Interestingly, the peel adhesion values on non-polar substrates such as polypropylene and polyethylene were measured as 9.65 ± 0.87 N/25 mm and 4.88 ± 1.52 N/25 mm, respectively, due to the van der Waals interaction. 45,46 In order to properly investigate the effect of temperature on peel strength, temperature-induced annealing should be evaluated in advance. The effect of annealing on peel adhesion was investigated by annealing the PSAs at different times.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the peel adhesion values on non-polar substrates such as polypropylene and polyethylene were measured as 9.65 ± 0.87 N/25 mm and 4.88 ± 1.52 N/25 mm, respectively, due to the van der Waals interaction. 45,46 In order to properly investigate the effect of temperature on peel strength, temperature-induced annealing should be evaluated in advance. The effect of annealing on peel adhesion was investigated by annealing the PSAs at different times.…”
Section: Resultsmentioning
confidence: 99%
“…In detail, when the fluctuation range of temperature and energy was from 5% to 10%, the system was considered to have reached equilibrium. [30][31][32][33] For example, Figure 5 illustrated the variation of density and energy of rubber system including the IR and the accelerator TiNTD during the NPT equilibrium. We found that the system reached a stable state after 200 ps, proving that the system has reached a state of equilibrium.…”
Section: The Building Process and Molecular Dynamicsmentioning
confidence: 99%
“…2 Waterborne latex-based PSAs are often made from n-butyl acrylate or 2-ethylhexyl acrylate and have small amounts of comonomers which can provide high T g segments (routinely styrene or methyl methacrylate) as well as comonomers which can promote wetting and adhesion, or secondary reversible interactions to improve cohesion (for example (meth)acrylic acid). [3][4][5][6] Commercially, these PSAs are used for labels. A typical label has several layers: a topcoat, a facestock with a printed image or text, the PSA, and a liner which contains a release coating, often made using high molecular weight silicones, to facilitate its removal before application.…”
Section: Introductionmentioning
confidence: 99%
“…2 Waterborne latex-based PSAs are often made from n -butyl acrylate or 2-ethylhexyl acrylate and have small amounts of comonomers which can provide high T g segments (routinely styrene or methyl methacrylate) as well as comonomers which can promote wetting and adhesion, or secondary reversible interactions to improve cohesion (for example (meth)acrylic acid). 3–6…”
Section: Introductionmentioning
confidence: 99%